Caracterización morfo-cultural e identificación molecular de comunidades bacterianas de la cuenca hidrográfica El Carmen- Loja - Rodríguez Díaz, Evelyng Gardenia (2016)
Microbasins are ecosystems of great environmental importance due to their huge biological diversity, landscape and cultural value and primarily due to their ability to store the liquid of live: water. Today efforts to direct studies that contribute to the knowledge of the biological communities that inhabit these types of ecosystems are redoubled. That is why this research aimed to characterize and compare bacterial communities in water and sediments samples of the microbasin "El Carmen" Loja, taking into account climatic variables and vegetation of the study area during the rainy season. Our study based on a diagnosis of environmental variables that are closely related to the proliferation of bacterial communities such as temperature, precipitation and riparian vegetation. Subsequently, quantification, morpho-cultural characterization and molecular identification of bacterial isolates from water and sediment was performed. The results show that there was a marked influence of environmental variables evaluated on the quantification and diversity of analysed microorganisms. However, it could be determined that the Rivera Quality Index (RQI) is taken as "Good", because all measured attributes were optimal. Analysing the quantification of bacterial communities’ reveals that exists in most of the samples a tendency to standardize the growth curve in the evaluated period except ESP2 B and ESP3 B for water and ESP1 B for sediment. The comparison between the two ravine, regarding Colonies Former Unit (CFU ml-1) in water samples, showed that in the Espumos ravine there is a 7.7% increase over El Carmen; whereas for sediment El Carmen beat Espumos in 31.1% of bacterial CFU g-1. Through morpho-cultural characterization it was determined that the most abundant appearance between bacterial communities was bearded, with a circular shape, convex elevation and flat or crushed, continuous whole edge, beige colour and Gram positive and Gram negative short rods. All these characteristics correspond to those genera belonging to Bacillus and Micrococcus. Molecular methods allowed the genomic DNA extraction and amplification of 16S rRNA gene for bacteria genetic identification at the species level; however, this activity could not be performed due to genomic sequencing couldn´t be performed